Why child allowances fail to solve the pension problem of aging societies - Peter Stauvermann; Frank Wernitz (Economies, 2019)
The aim of the paper is to investigate how child allowances affect population growth and pension benefits of pay-as-you-go (PAYG) pension systems in small open and closed economies. We apply an overlapping-generations (OLG) model in its canonical form, where we consider endogenous fertility and growth generated by human capital accumulation. From the analysis, we conclude that in a small open economy, child allowances increase the number of children, yet decrease pension benefits over the long run. If we consider a closed economy, the effect of child allowances on fertility is ambiguous and remains negative on pension benefits over the long run.
Keywords: 330; child allowances; fertility; human capital; OLG model; PAYG pension system